Heuristic approach to solution of unit commitment for electrical system / Azizan Harun - Harun, Azizan (1996)
This paper describes in general view of the algorithm developed for a unit commitment solution for electrical system. The unit commitment program optimizes the shutdown and generation cost so as to achieve minimum system fuel costs. The program is flexible and considers numerous special operating restrictions or constraints. This program applies the heuristic approach, formulated and coded in Turbo C.